Investigation of the Thermal Performance of Salt Hydrate Phase Change of Nanoparticle Slurry Flow in a Microchannel - Safi A. Memon; M. B. Sajid; M. S. Malik; Awad B. S. Alquaity; M. Mohib ur. Rehman; Taqi A. Cheema; Moon Kyu Kwak; Cheol Woo Park (Journal of Chemistry)
Computational study was conducted to investigate the thermal performance of water-based salt hydrate S44 nanoparticles as the phase change material (PCM) in a microchannel heat sink. Constant heat dissipation was applied on the top wall of the heat sink. Forced internal convection of the PCM slurry flow was performed through a homogeneous approach. Three thermal performance parameters, including effectiveness ratio, performance index, and Merit number, were used to quantify the cooling performance of S44 for various concentrations of the PCM nanoparticles. The thermal performance of the salt hydrate S44 slurry was also compared with a similar study conducted for lauric acid nanoparticle slurry found in the literature. Specific operating conditions were identified. The salt hydrate S44 would provide better thermal performance than lauric acid, and vice versa. Finally, Nusselt number correlations have been developed for the microchannel PCM heat sink for Reynolds numbers in the range 12.23 to 47.14 and Prandtl numbers in the range 3.74 to 5.30. A design guideline for manufacturing PCM particles and microchannel heat sinks is provided. With this guideline, the heat absorption ability of the heat sink is maximized, and the pumping power and the losses related to the addition of the particles are minimized.